Applied psychology - Coolican, Hugh. (London : Hodder Arnold, 2007)
This edition is fully updated with all the latest developments within the applied psychology fields. It covers both the theoretical background and the practical day-to-day aspects of a career in psychology. It also contains a new chapter on counselling.
Previous ed.: London: Hodder & Stoughton, 1996.
Includes bibliographical references (p. 281-306) and index.
Keywords: Psychology, Applied; Psychology